The Other Hand of God: The Holy Spirit as the Universal Touch and Goal - Kramer, Victor Anthony (Cistercian studies quarterly, 2004)
Reviews the book "The Other Hand of God: The Holy Spirit as the Universal Touch and Goal," by Kilian McDonnell.